Analysis of an ideal composition tunable combined cooling and power cycle with CO2-based mixture. (15th September 2022) - Sun, Xiaocun; Shi, Lingfeng; Tian, Hua; Wang, Xuan; Zhang, Yonghao; Yao, Yu; Sun, Rui; Shu, Gequn
Abstract: Thermodynamic cycle can realize maximum efficiency when temperature profiles of working fluid and heat source/sink match exactly, such as Carnot cycle and Lorenz cycle. Ascribed to the discrepancy of real working fluid and ideal working fluid, generally, the best temperature match of different heat exchange processes cannot be obtained meantime. To surmount this issue and give full play to zeotropic mixtures' advantage, transformation of combined cooling and power cycle after introducing composition adjustment is discussed in this study. The phenomenon of temperature mismatch happened in a composition-fixed combined cycle is investigated first, it shows that optimal mixture compositions among various heat exchange processes are disparate. Then, an ideal composition tunable combined cycle is evaluated without considering the specific adjustment process; results show that, under the same cooling requirement, net power output of the combined cycle could be improved by 3.93% owing to the adjustment of composition operated in sub-cycles and enhanced temperature match. To realize the required composition obtained during ideal analysis, a two-step composition adjustment method is proposed and the desired composition could be acquired by suitable separation quality and rebuilding proportion. However, due to the restraint of pinch point, the practical composition tuning structure could realize 2.30% improvement. Highlights: Optimal compositions for various heat exchange processes are disparate. Potential of composition adjustment is proved by an ideal composition tunable structure. A two-step composition adjustment method is proposed to obtain required compositions. Performance of practical composition tuning structure is restricted by pinch point.